A nuclear localization for Avr2 from Fusarium oxysporum is required to activate the tomato resistance protein I-2 - Ma, Lisong; Cornelissen, Ben J.; Takken, Frank L. (Frontiers in Plant Science, 2013)
Plant pathogens secrete effector proteins to promote host colonisation. During infection of tomato xylem vessels, Fusarium oxysporum f. sp. lycopersici (Fol) secretes the Avr2 effector protein. Besides being a virulence factor, Avr2 is recognised intracellularly by the tomato I-2 resistance protein, resulting in the induction of host defences. Here, we show that AVR2 is highly expressed in root- and xylem-colonising hyphae three days post inoculation of roots. Co-expression of I-2 with AVR2 deletion constructs using agroinfiltration in Nicotiana benthamiana leaves revealed that, except for the N-terminal 17 amino acids, the entire AVR2 protein is required to trigger I-2-mediated cell death. The truncated Avr2 variants are still able to form homo-dimers, showing that the central region of Avr2 is required for dimerization. Simultaneous production of I-2 and Avr2 chimeras carrying various subcellular localization signals in N. benthamiana leaves revealed that a nuclear localization of Avr2 is required to trigger I-2-dependent cell death. Nuclear exclusion of Avr2 prevented its activation of I-2, suggesting that Avr2 is recognised by I-2 in the nucleus.